The Influence of Global and Growth Mindsets on Organizational Commitment and Educational Staff Performance at Universitas Warmadewa: Advancing Towards a High-Quality and Globally Competitive University - Sugiati, Gusti Ayu; Sudarmini, Ketut; Rustini, Ni Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aimed to examine the effects of global mindset, growth mindset, and organizational commitment on the performance of educational staff at Universitas Warmadewa, striving to realize its vision of becoming a high-quality, ecotourism-oriented, and globally competitive institution by 2034. The sample included 71 participants. Data were collected through questionnaires and analyzed using Smart PLS. The results indicated that: 1) Global mindset significantly positively affected organizational commitment but had an insignificant negative effect on performance. 2) Growth mindset significantly positively influenced both organizational commitment and performance. 3) Organizational commitment significantly positively impacted performance. 4) Global mindset influenced performance through organizational commitment, which fully mediated this relationship. 5) Growth mindset also influenced performance through organizational commitment, which partially mediated this relationship.